Design and rationale of the NetherLands registry of invasive Coronary vasomotor Function Testing (NL-CFT). (15th May 2023) - Crooijmans, C.; Jansen, T.P.J.; Konst, R.E.; Woudstra, J.; Appelman, Y.; den Ruijter, H.M.; Onland-Moret, N.C.; Meeder, J.G.; de Vos, A.M.J.; Paradies, V.; Woudstra, P.; Sjauw, K.D.; et al.
Abstract: Background: Angina without angiographic evidence of obstructive coronary artery disease (ANOCA) is a highly prevalent condition with insufficient pathophysiological knowledge and lack of evidence-based medical therapies. This affects ANOCA patients prognosis, their healthcare utilization and quality of life. In current guidelines, performing a coronary function test (CFT) is recommended to identify a specific vasomotor dysfunction endotype. The NetherLands registry of invasive Coronary vasomotor Function testing (NL-CFT) has been designed to collect data on ANOCA patients undergoing CFT in the Netherlands. Methods: The NL-CFT is a web-based, prospective, observational registry including all consecutive ANOCA patients undergoing clinically indicated CFT in participating centers throughout the Netherlands. Data on medical history, procedural data and (patient reported) outcomes are gathered. The implementation of a common CFT protocol in all participating hospitals promotes an equal diagnostic strategy and ensures representation of the entire ANOCA population. A CFT is performed after ruling out obstructive coronary artery disease. It comprises of both acetylcholine vasoreactivity testing as well as bolus thermodilution assessment of microvascular function. Optionally, continuous thermodilution or Doppler flow measurements can be performed. Participating centers can perform research using own data, or pooled data will be made available upon specific request via a secure digital research environment, after approval of a steering committee. Conclusion: NL-CFT will be an important registry by enabling both observational and registry based (randomized) clinical trials in ANOCA patients undergoing CFT. Highlights: NL-CFT is a web-based, prospective, observational registry. All consecutive ANOCA patients undergoing clinically indicated CFT are included. NL-CFT enables both observational and registry based (randomized) clinical trials.